c.1 - Saksena, K. D. (Delhi, 2005)
It analyses the performance of the Indian economy during a decade of wide ranging economic reforms, which commenced in mid-1991, as compared to its behaviour in the eighties when some piecemeal measures of liberalization had been taken. Starting with an overview, the book comprehensively covers Important aspects like GDP and Employment Growth, Human Development, Poverty Alleviation, Privatization, Savings and Investment (including foreign investment), Agriculture, Industry, Resource Mobilisation by the Government, Public Expenditure, Deficit Financing, External Debt, Foreign Trade, Balance of Payments and Behaviour of Prices. A comparative study of economic growth in India and China during the reforms period has been made to draw lessons from the Chinese experience. Inter-state disparities in development (including rural and urban and gender disparities), and inter-state variations in public expenditure patterns and their have also been analysed. The entire study is based primarily on empirical evidence relating to two decades, the eighties and the nineties, collected from various authoritative national and international sources.
Keywords: Economic development-India